Referencing Words in Surah Al-Nabba: Linguistic Study in Light of Text Linguistics - Abdulrazak, Omraan Mohamad; Al-Azazmeh, Mahmmud Hussein (Journal of Arabic Language Sciences and Literature, 2023)
In its general structure, the text is based on a set of links linking and connecting with one another by means of explicit words thereby comprising a well-structured and coherent text.Linguists call these words as "Referencing Elements". The pronouns are considered as the most important of these "Referencing Elements" by which the text sentences are linked. The pronoun's reference is called "The Element Referred To". Referencing provides a semantic linking reflecting the interaction between both parts of such reference (The Element Referred To and the Referring Pronoun) which very often have such mutual links between them in terms of form and reference.The most important issue which influences the text as a model linguistic structure is the positions of Referencing Elements which have various kinds and types depending on the text subject matter of study. This research examines the kinds of the positions of such referencing elements in Surah Al-Nabba.
Keywords: Referencing Elements; Pronouns; Word Referred to; Referencing; Links; Connotation